Inventarisasi Anggrek (Orchidaceae) di Kawasan Taman Wisata Alam Bukit Tangkiling Kalimantan Tengah - Erna Wati; Sunariyati, Siti; Panjaitan, Desimaria (Konservasi Hayati, 2024)
Orchid (Orchidaceae) is one among the plants that grow in Taman Wisata Alam (TWA) Bukit Tangkiling, Central Kalimantan. The lack of information about orchid species in that area makes an inventory crucial. The purpose of this study was to inventory the species of orchids in the TWA Bukit Tangkiling area, as well as to learn about the environmental characteristics and distribution patterns of these plants. The research was conducted from October 2022 to March 2023. This research used the exploratory method and the sample was taken using the purposive sampling technique. Seven orchid species were identified as a result of this study: Acriopsis sp., Arachnis sp., Cymbidium finlaysonianum, Dendrobium crumenatum, Bulbophyllum purpurascens, Bromheadia finlaysoniana, and Dipodium pictum. Five species grow on plant stems (epiphytic), while two species grow on soil (terrestrial). Since each species was discovered less than 100 meters above sea level, they were all categorized as lowland orchid species. Dendrobium crumenatum is distributed randomly. The distribution of Bromheadia finlaysoniana, Bulbophyllum purpurascens, and Cyimbidium finlaysonianum is clustered. While the distribution pattern of the rest could not be determined because only one individual was found.